Dialogue of Life: An Experience in Leeds Community - Mohd Khambali @ Hambali, Khadijah (Jurnal Usuluddin, 2015)
Inter-religious dialogue among different ethnicity and social background is a unique experience especially for those who newly become a part of community in certain place. The dialogue of life among Leeds community begins when the different of ethnicity and social meet each other and share their daily life activities together. Through the process of dialogue which occurs in daily life interaction, the Leeds communities not only have a chance to know their counterparts but also have an opportunity to be closed contact with different faiths community. The interaction between the various communities with various faiths is significant to help enhance understanding in a structured manner through various activities and events as offered such as by Leeds Cultural Community Center, Leeds Grand Mosque as well as a mechanism to build a social integration among the community.